Growth, survival and net yield of milkfish chanos chanos, Forskal (1775) reared in floating net cages at different stocking densities - Humilde, Primo M. (College of Fisheries and Ocean Sciences, U. P. in the Visayas, 2001)
This study determined growth, survival and production of milkfish (Chanoschanos) reared in floating net cages for 120 days at stocking densities of 12.5, 25, 50 and 100 individuals per cubic meter. Growth was inversely proportional with stocking density but differences were not significant among treatments. Survival on the other hand was almost similar in all the densities tested (99.33-99.83%). Production however, markedly increased with increasing density (P<0.01). Although incremental changes in production progressively increased with increasing density, it started declining beyond 50/m3 corresponding to the observed marked decrease in growth of fish reared at this density.The use of sinking pellets while theoretically should allow individuals at the bottom to have access to food because of vertical feed dispersion, seemed to favour only individuals that could manage to stay at the surface during feeding. A combination of floating and sinking pellets could perhaps increase food access and thus improve growth of populations reared at higher densities. Also, the practice of hand feeding may limit feed distribution and it is not very effective especially when it is raining, during hot days or when the sea condition is not good. However, this problem might be addressed by using mechanized feed spreader. Results indicated that stocking density of milkfish could be further increased to the level when profitability starts to diminish with the declining growth of fish at higher population densities.